Non-utilization Is Not the Best Way to Manage Lowland Meadows in Hulun Buir - Ji, Guoxu; Li, Bing; Yin, Hang; Liu, Guofu; Yuan, Yuying; Cui, Guowen (Frontiers in Plant Science, 2021)
Carex meyeriana lowland meadow is an important component of natural grasslands in Hulun Buir. However, in Hulun Buir, fewer studies have been conducted on C. meyeriana lowland meadows than on other grassland types. To determine the most appropriate utilization mode for C. meyeriana lowland meadows, an experiment was conducted in Zhalantun city, Hulun Buir. Unused, moderately grazed, heavily grazed and mowed meadow sites were selected as the research objects. The analysis of experimental data from four consecutive years showed that relative to the other utilization modes, mowing and moderate grazing significantly increased C. meyeriana biomass. Compared with non-utilization, the other three utilization modes resulted in a higher plant diversity, and the moderately grazed meadow had the highest plant community stability. Moreover, principal component analysis (PCA) showed that among the meadow sites, the mowed meadow had the most stable plant community and soil physicochemical properties. Structural equation modelling (SEM) showed that grazing pressure was less than 0.25 hm2/sheep unit and that plant biomass in C. meyeriana lowland meadow increases with increasing grazing intensity, temperature and precipitation.